Efektivitas Kombinasi POC Azolla microphylla dan Ampas Teh terhadap Pertumbuhan Tanaman Kangkung (Ipomea reptans Poir) - Dyah Ratna Wuryandari; Aminah Asngad (Bioscientist : Jurnal Ilmiah Biologi, 2023)
Water spinach (Ipomea reptans Poir) is a horticultural product that has high economic and nutritional value for the health of the human body. This research was conducted to determine the effectiveness of the combination of POC Azolla microphylla and tea dregs on the growth of water spinach plants. The research method used was an experiment with a completely randomized design (CRD) with 2 factors including the volume of POC administration which consisted of 4 levels (V0 = control, V1 = 150 ml, V2 = 250 ml, and V3 = 250 ml) and the time interval for giving POC. consists of 2 levels (I1 = 3 days, and I2 = 6 days). The parameters used in this study were plant height, number of leaves, and wet weight. Data were analyzed using Kruskal Wallis. The results showed that giving a volume of 250 ml of POC at intervals of 6 days gave the best results with an average plant height of 8.6 cm, 3 leaves and 0.86 gram fresh weight. Based on this, it can be concluded that the application of liquid organic fertilizer combination of Azolla microphylla and tea dregs is effective for the growth of water spinach plants.